(untitled) - Alex Tilbury (Cambridge, 2011)
English Unlimited is a six-level goals-based course for adults. Centred on purposeful, real-life objectives, it prepares learners to use English independently for global communication. Through universal topics and activities, and a focus on intercultural competence as a 'fifth skill', this international coursebook helps learners become more sensitive, more effective communicators. Teaching natural, dependable language, and with CEF goals at its core, it brings real life into the classroom and gives learners the skills and strategies to communicate confidently outside it. Explore sections provide the extra ingredients for enhancing communicative ability, from further development of speaking skills to independent learning strategies. The e-Portfolio DVD-ROM enables learners to create a 'can-do' record of their work and progress. It also provides reference tools and a vocabulary trainer
Keywords: English language; English language; English language